Teacher’s Class Management Skills for Class V Thematic Learning Students at SD Khatolik St. Vincentius Noongan - Umbase, Ruth Sriana; Waldi, Atri; Tuerah, Paulus Robert; Hutapea, Yeni Tria; Damar, Hanrice Agustina; Bagit, Vidya; Mesra, Romi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Thematic learning is an integrated learning that focuses on student involvement in the learning of each sub-theme. The research in this paper is to uncover and explain the teacher's skills in managing the class for the fifth-grade students' thematic learning at SD Khatolik St. Vincentius Noongan. The researchers used qualitative research methods with data collection methods in the form of observation, interviews, and documentation. Data analyses were data reduction, data presentation, and conclusion drawing. The research result indicates that there are two types of class management in theme learning, non-physical and physical class management. Caring, firmness, change, and high standards comprise non-physical classroom management. Meanwhile, physical classroom management entails rearranging the blackboard's position, seating adjustment, bulletin boards, and window rearrangement in the classroom. Thematic learning is unusual in that it takes a teacher's inventiveness to manage the class. Of course, this management is dependent on the qualities and requirements of the pupils. Because each student's demands are unique, we must make the class as appealing as feasible while managing it.